Methods to Evaluate Pilots' Cockpit Communication: Cross-Recurrence Analyses vs. Speech Act–Based Analyses. (December 2017) - Gontar, Patrick; Fischer, Ute; Bengler, Klaus
The training and evaluation of the crew resource management skills of pilots play an essential role in increasing flight safety, as they aim to reduce human error in aviation operations. Communication between pilots is a critical crew resource management skill, as flying an airplane requires coordinated action and collaboration by the flight deck crew. However, research that studied flight instructors' agreement in (and, thus, the accuracy of) their evaluation of pilots' communication behavior found little consistency in their judgments. As such, the present research explores the feasibility of a content-free approach—cross-recurrence analysis—to assess crew communication, in contrast to commonly employed content-based approaches that are grounded in speech act analysis. Results indicate that cross-recurrence analysis can identify communication patterns associated with high and low crew performance. We discuss the implications that these results may have for future research and communication assessment in pilot training.